Feasibility and acceptability of a Takeaway Masterclass aimed at encouraging healthier cooking practices and menu options in takeaway food outlets. Issue 12 (August 2019) - Hillier-Brown, Frances; Lloyd, Scott; Muhammad, Louise; Summerbell, Carolyn; Goffe, Louis; Hildred, Natalie; Adams, Jean; Penn, Linda; Wrieden, Wendy; White, Martin; Lake, Amelia; Moore, Helen; et al.
Abstract: Objective: To evaluate the feasibility and acceptability of the Takeaway Masterclass, a three-hour training session delivered to staff of independent takeaway food outlets that promoted healthy cooking practices and menu options. Design: A mixed-methods study design. All participating food outlets provided progress feedback at 6 weeks post-intervention. Baseline and 6-week post-intervention observational and self-reported data were collected in half of participating takeaway food outlets. Setting: North East England. Participants: Independent takeaway food outlet owners and managers. Results: Staff from eighteen (10 % of invited) takeaway food outlets attended the training; attendance did not appear to be associated with the level of deprivation of food outlet location. Changes made by staff that required minimal effort or cost to the business were the most likely to be implemented and sustained. Less popular changes included using products that are difficult (or expensive) to source from suppliers, or changes perceived to be unpopular with customers. Conclusion: The Takeaway Masterclass appears to be a feasible and acceptable intervention for improving cooking practices and menu options in takeaway food outlets for those who attended the training. Further work is required to increase participation and retention and explore effectiveness, paying particular attention to minimising adverse inequality effects.